Accompaniment of Contextual Learning Oriented Minimum Competency Assessment of Mathematics through Lesson Study - Inganah, Siti; Utomo, Dwi Priyo; Baiduri, Baiduri; Djunaidi, Arif (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2023)
Minimum Competency Assessment is a component of the assessment as an assessment policy established by the Indonesia government in independent learning to assess the success of formal education in schools. The junior high school of Muhammadiyah 8 Batu has implemented learning innovations. However, it still needs to be improved, especially in integrating the involvement of students in creative and critical thinking, communication, and collaboration, and refers to the Minimum Competency Assessment. This Lesson Study mentoring activity aims to improve the quality of learning mathematics by using a contextual approach oriented to Minimum Competency Assessment. This mentoring activity used workshop and simulation methods. Four mathematics teachers attended the workshop and simulation. The results showed that the Lesson Study team produced a Minimum Competency Assessment for six grade 7 groups oriented contextual learning design that integrated students’ involvement in creative and critical thinking, communication, and collaboration, which was realized through lesson design. Model teachers and observers were enthusiastic and carried out Minimum Competency assessment-oriented contextual learning activities through Lesson Study well. Students gave a positive response and were very active while participating in learning. The mentoring activities of Minimum Competency Assessment-oriented contextual learning can be said to be effective. The learning designs prepared by the teacher can be implemented in other classes with relatively the same student characteristics.